Gestión de inventario del Almacén Credifacil, ubicado en el Cantón Montalvo, período 2022 - Andrade Monar, Henrry Flamel (2023)
The present case study that was developed in the Credifacil warehouse, located in the Montalvo canton with the purpose of analyzing inventory management for the construction of improvement strategies. The research was carried out considering the descriptive research methodology in which the shortcomings of the company were organized, summarized and analyzed. Inventory management is responsible for monitoring the products and acquiring what is necessary to maintain an adequate stock, therefore, it will provide accurate information on the shortcomings of the warehouse and providing possible solutions that can be applied for improvement. In the investigation carried out in the Credifacil warehouse, I have the following results: they do not have control of the entrances and exits of the products from the warehouse, there is no database that shows the stocks of the products in the warehouse, lack of implementation of new stock techniques.